2023
DOI: 10.1108/jfc-11-2022-0292
|View full text |Cite
|
Sign up to set email alerts
|

When internal organizational factors improve detecting corruption in state-owned companies

Abstract: Purpose The phenomenon of corruption requires extra handling to achieve zero corruption. The purpose of this paper is to examine the integrated governance, risk management and compliance (GRC) implementation, the quality of internal audits and management's commitment to improving the ability to detect corruption and its impact on the company's financial performance. Design/methodology/approach This paper used primary and secondary data. Financial statement data and survey results from participants in 69 stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
0
0
0
Order By: Relevance
“…Researchers and practitioners, especially in the Nigerian economy, explain that organizational resilience has embedded complexity that requires managers to use skills to address critical concerns such as whistleblowing. These may include compliance with rules of engagement, provision of resources needed to respond and effective time management with the broad intention to address emerging whistleblowing incidents (Figure 1; Siahaan et al. , 2023).…”
Section: Further Discussion On Identified Factors For Effective Whist...mentioning
confidence: 99%
“…Researchers and practitioners, especially in the Nigerian economy, explain that organizational resilience has embedded complexity that requires managers to use skills to address critical concerns such as whistleblowing. These may include compliance with rules of engagement, provision of resources needed to respond and effective time management with the broad intention to address emerging whistleblowing incidents (Figure 1; Siahaan et al. , 2023).…”
Section: Further Discussion On Identified Factors For Effective Whist...mentioning
confidence: 99%
“…Performance, as articulated by Gartenberg et al (2019), encapsulates the financial well-being of an organization and serves as an indicator of its overall operational health. Operational performance, highlighted by Siahaan et al (2023), is a specific facet that evaluates an organization's efficiency in creating and delivering products to customers, emphasizing quality and timeliness as key factors. Richard et al (2019) elucidate that corporate performance encompasses financial metrics like profit growth, return on assets, and return on investment, offering a holistic view of a company's outcomes.…”
Section: The Concept Of Performancementioning
confidence: 99%
“…The implementation of corporate governance in state-owned enterprises is deemed to be less effective in preventing corruption (Chen et al, 2016;Harahap & Riyanto, 2020). Using a stateowned enterprises sample, it is observed that the implementation of corporate governance, including risk management and compliance, has a positive influence on the capability of the firms to detect corruption (Siahaan et al, 2023). It is argued that the power extension of government allows state-owned enterprises to exercise various breaches to utilize the political influence or favoritism for the benefit of a group of people who share the same value in the government and state-owned enterprises (Baum et al, 2019).…”
Section: Literature Review and Hypo-mentioning
confidence: 99%